Deep Eddy Kinetic Energy in the Tropical Pacific From Lagrangian Floats. Issue 8 (19th August 2020) - Delpech, A.; Cravatte, S.; Marin, F.; Ménesguen, C.; Morel, Y.
Abstract: At the ocean surface, satellite observations have shown evidence of a large spectrum of waves at low latitudes. However, very little is known about the existence and properties of the deep variability. Most of the subsurface observations rely on localized measurements, which do not allow for a global estimation of this variability. In this study, we use velocity estimates, provided by Argo float drifts at 1, 000 m, to analyze the spatial and temporal distribution of the deep eddy kinetic energy (EKE) and its spectral signature with an unprecedented time and space coverage. In the tropical Pacific, high EKE is found along the equator, at the western boundary and poleward of 7°N. EKE meridional distribution is also found to vary at the scale of the meridionally alternating mean zonal jets: it is higher inside eastward currents. We develop an original statistical scale analysis to determine the temporal and spatial scale dependence of this deep EKE footprint. We show the presence of periodic features whose characteristics are compatible with theoretical equatorial waves dispersion relations. Annual and semiannual Rossby waves are observed at the equator, as well as ∼30‐day Yanai waves, consistent with surface tropical instability waves. The location and intensification of these waves match the downward energy propagation predicted by ray tracing linear theory. Short‐scale variability (with ∼70‐day periods and 500‐km wavelength) has also been detected poleward of 7°N. The generation mechanisms of this variability are discussed, as well as its potential importance for the mean circulation. Plain Language Summary: Energy in the deep ocean is important as it is a potential driver of the deep circulation, which has important climate feedbacks. Because of its singular dynamics, the equatorial ocean is a preferential region of transfer of energy from the surface to the interior of the ocean. Very little is known, however, about the energy content in the deep equatorial oceans. In this study, we use the large number of floats, called Argo floats, drifting at 1, 000‐m depth in the ocean to describe the deep kinetic energy in equatorial regions. We show that various energetic waves are present at 1, 000 m in the tropical Pacific, and we discuss their potential generation mechanisms as well as their implications for the circulation. These new observations may help to validate some theories or numerical simulations of the deep equatorial and tropical circulation. Key Points: Eddy kinetic energy at 1, 000 m in the tropical Pacific is investigated using Argo float drifts Deep intra‐annual variability is evidenced with 30‐day period and 1, 000‐km wavelength at the equator and 70‐day period, 500 km off the equator Eddy kinetic energy exhibits small‐scale features, suggesting interactions with the mean jet‐like circulation at 1, 000 m